2009
DOI: 10.1088/0004-637x/700/1/358
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation in Disk Galaxies. I. Formation and Evolution of Giant Molecular Clouds via Gravitational Instability and Cloud Collisions

Abstract: We investigate the formation and evolution of giant molecular clouds (GMCs) in a Milky-Way-like disk galaxy with a flat rotation curve. We perform a series of 3D adaptive mesh refinement (AMR) numerical simulations that follow both the global evolution on scales of ∼ 20 kpc and resolve down to scales 10 pc with a multiphase atomic interstellar medium (ISM). In this first study, we omit star formation and feedback, and focus on the processes of gravitational instability and cloud collisions and interactions. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
359
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(398 citation statements)
references
References 82 publications
(119 reference statements)
34
359
5
Order By: Relevance
“…Global galactic simulations have shown that in a flat rotation curve disk, GMC collision timescales are relatively frequent, at  t t 0.2 coll orbit (Tasker & Tan 2009;Dobbs et al 2015).…”
Section: Sfr Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Global galactic simulations have shown that in a flat rotation curve disk, GMC collision timescales are relatively frequent, at  t t 0.2 coll orbit (Tasker & Tan 2009;Dobbs et al 2015).…”
Section: Sfr Gasmentioning
confidence: 99%
“…It is an attractive mechanism because it is a process that is expected to create ∼parsec-scale dense gas clumps that are prone to gravitational instability and are the precursors to star clusters, while at the same time being sensitive to global galactic dynamics, such as the shear rate (Tan 2000(Tan , 2010Tasker & Tan 2009;Suwannajak et al 2014) and the presence of spiral arms (Dobbs 2008). Such a connection to orbital shear naturally explains the dynamical Kennicutt-Schmidt relation (Kennicutt 1998;Leroy et al 2008), S µ S W…”
Section: Introductionmentioning
confidence: 99%
“…The high-density tail is where star formation takes place. Li et al 2005;Agertz et al 2009b;Tasker & Tan 2009). They have highlighted the role of gravity and turbulence in driving GMC formation.…”
Section: Resolved Star Formation In Cosmological and Galaxy-sized Modelsmentioning
confidence: 99%
“…Details of the disc initial conditions for simulations without star formation are described in Tasker & Tan (2009). Our highest resolution simulation has a smallest cell size of 7.8 pc and star particles were formed with typical masses of 10 3 M from gas with n H ,c > 100 cm −3 (i.e.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…They were tracked through the simulation by comparing outputs at 1 Myr intervals. Details of the cloud identification and tracking scheme are also described in Tasker & Tan (2009).…”
Section: Simulation Detailsmentioning
confidence: 99%